Pengaruh Komposisi Pupuk N, P Dan K terhadap Pertumbuhan dan Produksi Lada Pada Tanah Bekas Tambang Timah di Bangka - Yulius Ferry; Juniaty Towaha (Jurnal Tanaman Industri dan Penyegar, 2011)
The research aims to obtain composition optimum of the NPK fertilizers to the assembly for pepper in the after tin mining soil. A study was conducted in May to December 2009 at the home paranet  KP. Sukamulya, Sukabumi West Java with 350 m altitude above sea level. The design environment used is Complete Random Design (RAL) are arranged in factorial and repeated 3 times. The first factor is the composition of NPK nutrients are: P1) NPK 1: 1: 1; P2) NPK 2: 1: 2; P3) NPK 2: 2: 3, P4) 3: 2: 3. The second factor is the dose fertilizing, namely: D1) 10 g / plant; D2) 20g/plant; D3) 30 g / plant, and D4) 40 g / plant. Generally, the results showed that the composition of N, P and K fertilizers not yet shown significant  affect in all parameters of vegetative growth, except number of leaves. The dosage fertilizers 40 g/plant increases significantly to number of leaves but not significant in the other parameters of vegetative growth. The best of combination N, P and K fertilizers were 40g/application.